PRELIMINARY TRIAL ON THE EFFECT OF LEAVO-TETRAMISOLE ON VARIOUS INTESTINAL HELMINTHIASES IN IRAN - I. Farahmandian; F. Arfaa; G.H. Sahba; H. Jalali (Tehran University of Medical Sciences, 1974)
The effect of a new anthelmintic compound, Leavo-tetramisole, in the mass-treatment of several intestinal helminthes has been evaluated during a study undertaken among the population of the village of Zavieh Hajian, located about 10 km northwest of Dezful, Khuzestan.In the autumn of 1972, a total of 83 inhabitants, 65 of whom were simultaneously infected with Ascaris, hookworm (Ancylostoma) and Trichostrongylus spp. and 18 of whom where infected with the first two helminthes only, were treated with 40 mg tablets of the drug., The drug was given in a single dose of one tablet to the age group below 6, two tablets to the age group 6-15 and 3 tablets to adults. A group of 61 patients was kept as a control. Administration of the drug resulted in cure rates of 98.8% for Ascaris, 95.2% for Ancylostoma and 93.9% for trichostrongylus:, The reduction in the mean number of eggs among remaining cases was very high Low intensity side-effects, which were encountered among 20% of treated cases only, included, in order of frequency abdominal pain, headache, vertigo and vomiting. The high efficacy of this drug on 3 species of helminthes prevalent in the area, together with ifs effect in a single dose, make it the drug of choice for the mass-treatment of patients infected with helminthiasis in the southwestern part of Iran.